AN ANALYSIS OF STUDENTS’ ABILITY IN USING PREPOSITION WITHIN DESCRIPTIVE TEXT AT SEVENTH GRADE OF MTSN 6 AGAM - Fathul Muntazia; Eliza Eliza; Reflinda Reflinda; Loli Safitri (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Prepositions were part of grammar used in speaking, listening, reading and writing. In learning English, the students must be able to grasp the meaning. There were several problems that the researcher found in the process of learning English at seventh grade of MTSN 6 Agam. There first problem was the students did not know the meaning of the prepositions. The second problem was that students still found difficulties to distinguish preposition in arranging the sentence correctly. In fact, prepositions are of several types. Therefore, the purpose of this research was to find out how the students’ ability in using prepositions within descriptive text and which types of prepositions are most frequently misused by students’ in descriptive text. This research was a quantitative research. The population of this research was seventh grade students at MTSN 6 Agam which consists of 10 classes with total students 329, meanwhile the sample of this research 76 students. In this research, the researcher used purposive sampling. Instrument of this research was a test. The data had been of this research obtained, then analyzed, to find the percentage of ability. Regarding the result of the data analysis, the conclusion were types of prepositions are most frequently misused by students were prepositions place with 265 misused, and related to the second research question found that, students ability in using preposition within descriptive text have categories is sufficient 65%.